2021
DOI: 10.4235/agmr.21.0033
|View full text |Cite
|
Sign up to set email alerts
|

Frailty among Older Adults Living in Nursing Homes in Indonesia: Prevalence and Associated Factors

Abstract: Introduction: Frailty syndrome is a predictor of all-cause mortality among older adults living in nursing homes. Data about the prevalence of frailty among individuals living in nursing homes particularly in middle-income countries are limited. Thus, this study aimed to identify the prevalence of frailty and its associated factors among older adults living in nursing homes in Indonesia. Methods: A cross-sectional study of older adults living in six nursing homes in Indonesia was conducted between May 2019 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 19 publications
1
17
1
1
Order By: Relevance
“…In this study we confirmed that the overall prevalence of malnutrition in senior's nursing homes is high, as detected by all the nutritional screening/assessment tools used. This result is similar with other studies involving nursing homes for institutionalized senior citizens showing that nutritional personalized care is needed [14,15] and should be provided according to the results of screening/assessment tools, comorbidities, preferences, and habits of senior citizens. As expected, institutionalized elders present with a higher prevalence of nutritional risk/malnutrition compared to the day care population even when all tools are adjusted to age, sex, and MMS.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study we confirmed that the overall prevalence of malnutrition in senior's nursing homes is high, as detected by all the nutritional screening/assessment tools used. This result is similar with other studies involving nursing homes for institutionalized senior citizens showing that nutritional personalized care is needed [14,15] and should be provided according to the results of screening/assessment tools, comorbidities, preferences, and habits of senior citizens. As expected, institutionalized elders present with a higher prevalence of nutritional risk/malnutrition compared to the day care population even when all tools are adjusted to age, sex, and MMS.…”
Section: Discussionsupporting
confidence: 90%
“…The Short Form, available on Nestlé's website, was developed and validated specifically for an older population (>60 years) [2]. Completion of the MNA-SF results in a score with 3 categories: normal (12)(13)(14), risk of malnutrition (8)(9)(10)(11), and malnourished (0-7).…”
Section: Mini Nutritional Assessment Short Form (Mna-sf)mentioning
confidence: 99%
“…These factors are interconnected, form a cycle, and create conditions including inflammation, chronic malnutrition, and disturbance in hormone modulation and coagulation pathways. 2 Frailty is currently considered a geriatric syndrome due to the cumulative decline of multiple physiological systems leading to reduced physiological reserves and resistance to stressors, ultimately leading to detrimental outcomes such as falls, disability, hospitalization and death. 3 Both abnormal BMI and frailty might lead to disability among the elderly, therefore it is important to identify the elderly with frailty and disability as a part of comprehensive geriatric assessment.…”
Section: Muhammad Zuhal Darwismentioning
confidence: 99%
“…Usually, only the elderly with many comorbidities and lack of financial support move to nursing homes. 2 Physical frailty is highly prominent for the elderly who is living in nursing homes (range 19.0 to 75.6%) in western populations. Compared to community-dwelling elderly, individuals living in nursing homes may be more susceptible and often have various risk factors for frailty (i.e., activity of daily living disability, self-reported health status).…”
Section: Muhammad Zuhal Darwismentioning
confidence: 99%
“…Nursing home residents are a particularly vulnerable to frailty [ 13 , 20 ]. The main determinants of being physically frail in nursing home residents‘ are: malnutrition [ 21 ], vitamin D deficiency [ 22 , 23 ], older age, female, living in a private institution, living with unknown person or living alone, having no regular exercise (≤2 times/week) and sedentary behaviour, poor self-reported health, lower socioeconomic status, lack of educational qualifications, obesity, being a smoker, and pain [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%